2004
DOI: 10.1080/00015458.2004.11679647
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Intraperitoneal Repair of Incisional and Ventral Hernias

Abstract: Laparoscopic repair of incisional and ventral hernia is a safe alternative for open mesh repair. Further definition of indications is needed, based on the dimension and the localization of the hernia. If the omission of transabdominal wall sutures improves the postoperative course with no adverse effect on recurrence rate, will be the subject of a randomized trial we have started this year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…[203428] Left hypochondrium / subcoastal region has been found to be the preferred site for Verres needle insertion. [1828] Open Hassan technique[22] and Visiport were other alternatives used for access. [3225] To obtain triangulation, working ports are placed away from defect or lateral to the rectus muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[203428] Left hypochondrium / subcoastal region has been found to be the preferred site for Verres needle insertion. [1828] Open Hassan technique[22] and Visiport were other alternatives used for access. [3225] To obtain triangulation, working ports are placed away from defect or lateral to the rectus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…[3225] To obtain triangulation, working ports are placed away from defect or lateral to the rectus muscle. [121319202834]…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider giant or large wall defects to have a surface area of approximately 170 cm 2 (range 100e225 cm 2 ) 29,34 . In general, the operating time is longer for laparoscopic ventral hernia repair than for the classic open approach 37,38 , although some authors reported no difference in operation time when comparing the two techniques 43 . Others even reported a shorter operating time for laparoscopic repair 44 , depending mainly on the experience of the surgeon, use of tackers, bowel or omental adhesions, site, size and the number or multilocularity of the hernia defect.…”
Section: Discussionmentioning
confidence: 99%
“…This is a widely recognized complication of both open and laparoscopic hernia repair techniques. [1,4,7,[11][12][13]15,18,23,[25][26][27][28][29][30] Respondents in our survey approach this complication conservatively, that is by delay of mesh placement for several weeks. It is interesting to note that 3% would place mesh in a field regardless of the presence of spillage of enteric contents.…”
Section: Discussionmentioning
confidence: 99%